Mid-Pliocene climate change amplified by a switch in Indonesian subsurface throughflow - Karas, Cyrus; Nürnberg, Dirk; Gupta, Anil K.; Tiedemann, Ralf; Mohan, Kuppusamy; Bickert, Torsten (Nature Geoscience, 2009)
The tectonically driven closure of tropical seaways during the Pliocene epoch (approx5–2 million years (Myr) ago) altered ocean circulation and affected the evolution of climate. Plate tectonic reconstructions show that the main reorganization of one such seaway, the Indonesian Gateway, occurred between 4 and 3 Myr ago. Model simulations have suggested that this would have triggered a switch in the source of waters feeding the Indonesian throughflow into the Indian Ocean, from the warm salty waters of the South Pacific Ocean to the cool and relatively fresh waters of the North Pacific Ocean. Here we use paired measurements of the delta18O and Mg/Ca ratios of planktonic foraminifera to reconstruct the thermal structure of the eastern tropical Indian Ocean from 5.5 to 2 Myr ago. We find that sea surface conditions remained relatively stable throughout the interval, whereas subsurface waters freshened and cooled by about 4 °C between 3.5 and 2.95 Myr ago. We suggest that the restriction of the Indonesian Gateway led to the cooling and shoaling of the thermocline in the tropical Indian Ocean. We conclude that this tectonic reorganization contributed to the global shoaling of the thermocline recorded during the Pliocene epoch, possibly contributing to the development of the equatorial eastern Pacific cold tongue.